Association of oesophageal radiation dose volume metrics, neutropenia and acute radiation oesophagitis in patients receiving chemoradiotherapy for non-small cell lung cancer. Issue 1 (December 2016) - Everitt, Sarah; Duffy, Mary; Bressel, Mathias; McInnes, Belinda; Russell, Christine; Sevitt, Tim; Ball, David
Abstract Introduction The relationship between oesophageal radiation dose volume metrics and dysphagia in patients having chemoradiation (CRT) for non-small cell lung cancer (NSCLC) is well established. There is also some evidence that neutropenia is a factor contributing to the severity of oesophagitis. We retrospectively analysed acute radiation oesophagitis (ARO) rates and severity in patients with NSCLC who received concurrent chemotherapy and high dose radiation therapy (CRT). We investigated if there was an association between grade of ARO, neutropenia and radiation dose volume metrics. Material and methods Patients with NSCLC having concurrent CRT who had RT dose and toxicity data available were eligible. Exclusion criteria included previous thoracic RT, treatment interruptions and non-standard dose regimens. RT dosimetrics included maximum and mean oesophageal dose, oesophagus dose volume and length data. Results Fifty four patients were eligible for analysis. 42 (78 %) patients received 60 Gy. Forty four (81 %) patients received carboplatin based chemotherapy. Forty eight (89 %) patients experienced ARO ≥ grade 1 (95 % CI: 78 % to 95 %). ARO grade was associated with mean dose (rs = 0.27, p = 0.049), V20 (rs = 0.31, p = 0.024) and whole oesophageal circumference receiving 20 Gy (rs = 0.32p = 0.019). In patients who received these doses, V20 (n = 51, rs = 0.36, p = 0.011), V35 (n = 43, rs = 0.34, p = 0.027) and V60 (n = 25, rs = 0.59, P = 0.002) were associated with RO grade. Eleven of 25 (44 %) patients with ARO ≥ grade 2 also had ≥ grade 2 acute neutropenia compared with 5 of 29 (17 %) patients with RO grade 0 or 1 (p = 0.035). Conclusion In addition to oesophageal dose-volume metrics, neutropenia may also be a risk factor for higher grades of ARO.